Genetic aetiology of autosomal recessive non-syndromic hearing loss in sub-Saharan African patients: evaluation using targeted and whole exome sequencing - Lebeko, Kamogelo (Department of Pathology, 2019)
Hearing Loss (HL) is one of the highest contributors to disability worldwide. The highest incidence of the disease is seen in developing countries, such as those in subSaharan Africa (SSA). Patients affected with disabling HL are reported to be more than 466 million worldwide. The causes of HL can either be environmental or genetic with each contributing about 50% towards all cases, in many settings. In developing countries, the environment might contribute more due to poor health services and infrastructure available to the population. In the absence of environmental causes, there is a genetic component at play, that is largely unknown in African populations. Up to 70% of HL of genetic origin are non-syndromic (NS). The mode of inheritance is recessive in nearly 77% of non-syndromic HL. Up to date, more than 100 genes have been associated with HL harbouring more than 1000 causative variants. In many populations of European and Asian descent, pathogenic variants in GJB2 (connexin gene 26) and GJB6 (connexin gene 30) are a major contributor to autosomal recessive non-syndromic hearing loss (ARNSHL). Comprehensive hearing health care programs should cover genetic causes by providing molecular testing, and genetic counselling, specifically SSA where genes and mutations causing HL remain largely unknown. The aim of this project was thus to uncover the genetic causes of HL among patients’ cohorts from Cameroon and South Africa. This was addressed by 1) sequencing common variants in the most relevant genes in other populations (GJB2 and GJB6), 2) using a targeted gene panel to resolve HL in 10 multiplex families from Cameroon presenting with ARNSHL and negative for GJB2 and GJB6 mutations screening, 3) screening novel variants found in known genes in a cohort of 82 singleplex HL cases from Cameroon and South Africa, and lastly, 4) using Whole Exome sequencing to explore the two unresolved multiplex cases with and subsequent findings confirmed by functional studies, and also screened in 80 singleplex HL cases. The following findings are reported: GJB6, GJA1 mutations screening and literature review No GJA1 or GJB6 mutation was not found in multiplex and simplex cases of HL in both Cameroonians and South Africans. The review of the literature confirms that the prevalence of GJB2- or GJB6-related NSHL is approximating to zero in most subSaharan African populations. Targeted Exome Sequencing (OtoSCOPE) The targeted genes, panel that included 116 genes, was able to resolve 7 of 9 families (77.8%) which were successfully sequenced, with one family failing to be sequenced. The causative variants identified in the 7 resolved families were : 1) compound heterozygous c.5806_5808delCTC and c.5880_5882delCTT in MYO7A; 2) compound heterozygous c.646T>A (p.Phe216Ile) and c.38G>A (p.Arg13His) in LOXHD1; 3) homozygous c.766-2A>G in OTOF; 4) a deletion and a complex copy number variation in STRC; 5) compound heterozygous c.1678G>A (p.Asp560Asn) and c.2007C>A(p.Asp669Glu) in SLC26A4; 6) Homozygous c.1996C>T(p.Arg666Stop) in MYO7A; 7) compound heterozygous c.6399C>A(p.Asp2133Glu) and c.2000T>C (p.Met667Thr) in CDH23. Five out of 12 variants were novel. Screening of these causative variants in known genes, in 82 singleplex HL cases from Cameroon and South Africa was unable to resolve any of the cases: the variants were in either heterozygous in low frequency or absent. Bioinformatic pathways exploration of SNP data of known HL genes revealed an extensive network within the HL genes, with 10 identified as important nodes, including MYO7A. Most HL genes were found to be involved in two biological processes which were sensory perception of mechanical stimulus (GO: 0050954, p= 1.430e-8) and sound (GO: 0007605, p = 1.246e-8). The molecular functions of variants found within these genes were found to mostly fall within the binding (GO: 0005488) and/or structural molecule activity (GO: 0005198). Whole Exome sequencing Whole exome sequencing was performed on four of the nine multiplex families: the two families that were unresolved by targeted panel sequencing, and two previously resolved families that were used as positive controls for the variant annotation and filtering pipeline. The results were the resolution of 3/4 families, including the two- positive control. The previously unresolved “family 8” was found to harbour a novel variant within the GRXCR2 gene, a gene only associated with HL once before. The c.251delC variant was revealed through in silico studies to cause a premature stop codon at position 116 due to its frameshift effect. The screening of this variant in our cohort of 80 singleplex cases revealed one other unrelated HL patient harbouring this causative variant. Due to the limited literature on the gene and its protein, in silico studies were used to show the predicted secondary structure folding of the protein as well as potential protein binding regions. Analysis showed that the predicted loss of a stable region of the protein as well as that of a putative binding domain could explain the pathogenic nature of the variant. In vitro studies showed that the variant hindered the detection of the protein by way of a DDK tag downstream in the plasmid. Additionally, GFP-Tagged GRXCR2 showed altered expression pattern in the variant when compared to the wildtype. In summary, our data has revealed the efficacy of using next generation sequencing tools in resolving HL among sub-Saharan African patients as opposed to the single candidate gene approach. In our quest, we have employed two widely used strategies, targeted panel and whole exome sequencing (WES), both of which have had great successes in various populations. The targeted approach was able to resolve 77.8% of our families but did not detect variants for two of the families revealing the presence of other variants harboured in rarely associated gene not captured or included on the panel. This prompted for the use of a more comprehensive approach such as WES. These results corroborated with those of two families previously resolved by targeted exome sequencing. Additionally, one of the previously unresolved family was now resolved. This showed that WES was sensitive enough to detect variants in known HL genes but comprehensive enough to detect variants in other regions of the exome which have not been associated with HL or rarely associated with HL. The benefit of WES also extends to the contribution of exomic data from patients of African descent as there is an underrepresentation of this group in exome repositories as well as genomic or SNP databases. To the best of our knowledge, this is the first study to use WES to resolve HL in patients of African descent. The other benefit of such a venture is the use of this data not only for patients in SSA but also those in the diaspora. In conclusion, we have successfully demonstrated the feasibility of using NGS tools in identifying causative variants in HL patients in SSA. Additionally, we have shown that WES is a more suitable approach to trying to resolve HL in Africa. Therefore, the data strongly support that genetic studies on families segregating HL in SSA could be the next frontier of HL genetic research, of global importance through discovering novel variants in known genes, and potentially novel genes. These studies will improve HL genetic diagnosis, retrospective counselling and testing, prevention and care including future prediction of treatment outcomes in sub-Saharan Africans, and in people of African descent.